A map to paradise - Meissner, Susan, 1961- (Berkley, 2025)
"1956, Malibu, California. Something is not right on Paradise Circle With her name on the Hollywood blacklist and her life on hold, out-of-work starlet Melanie Cole has little choice in company. There is her next-door neighbor and successful screenwriter, Elwood, but his agoraphobia only allows for short conversations through the windows. He's the closest thing she has to a friend in her exile, however, as she and her maid, Eva, an immigrant from Eastern Europe, rarely make conversation. Until they both happen to spot Elwood's sister-in-law and caretaker, June, digging in his rose garden one morning just before dawn. After that, they don't see Elwood at all anymore. Where could a man who never leaves the house possibly have gone? Has something happened to Elwood? The two women can't help trying to find out. But as they sneak up on and into June's life, they discover an unexpected secret, and then a shared goal that's even more startling"--